Motor racing, tobacco company sponsorship, barcodes and alibi marketing - Grant-Banham, Bruce; Britton, John (BMJ Publishing Group, 2011)
Abstract Background Sponsorship of Formula One (F1) motor racing, which has been used as an indirect medium of tobacco advertising for several decades, was prohibited by the 2005 European Union Tobacco Advertising Directive. Most F1 tobacco sponsorship of motor racing in the EU has since ceased, with the exception of the Scuderia Ferrari team, which continues to be funded by Philip Morris. In 2007, the Marlboro logo on Ferrari cars and other race regalia was replaced by an evolving ‘barcode’ design, which Ferrari later claimed was part of the livery of the car, and not a Marlboro advertisement.